Correction: pUL21 is a viral phosphatase adaptor that promotes herpes simplex virus replication and spread. - Tomasz H Benedyk; Julia Muenzner; Viv Connor; Yue Han; Katherine Brown; Kaveesha J Wijesinghe; Yunhui Zhuang; Susanna Colaco; Guido A Stoll; Owen S Tutt; Stanislava Svobodova; Dmitri I Svergun; et al. (PLoS Pathogens, 2022)
[This corrects the article DOI: 10.1371/journal.ppat.1009824.].